Design and fabrication of knee pad - Nasirul Muzaffar, Nasri (2013)
In this study, there are five natural fibers that is kenaf fiber, coconut pulp fiber, pineapple leaf fiber, palm oil fiber, and saw dust with two additional hybrid materials that is thermoplastic elastomer (TPE) mixed with kenaf fiber, and thermoplastic elastomer (TPE) mixed with pineapple leaf fiber, were being tested in term of deformation rate of these seven materials after being used to fabricate a knee pad prototype The use of these natural fibers as the knee pad materials, are actually a new findings, because these natural fiber are low in price, can be easily obtained and has a good mechanical properties. With this research, the commercial knee pad sold on the market can already be improved in terms of their strength towards the impact force. This study focused on fiber strength when the impact force of a ball is hitting on knee pad surface. During the drop ball experiment, which is conducted on a force plate and using a high speed camera to capture a picture of the ball hitting the knee pad, to all of the knee pad made up from the five fibers, with two additional hybrid fiber material, the best result is shown by the thermoplastic elastomer (TPE) mixed with kenaf fiber, in which it has less deformation compared to the other six materials, and this means that it has the high strength to resist the impact force that are hitting on it. In addition, in this study, we also concern about the comfort of the football athletes that are wearing these knee pad prototype through a survey of from the ten football athletes, during kicking the ball